STUDI PENENTUAN KANDUNGAN SULFUR (SULPHUR ANALYSIS) DALAM BATUBARA PADA PT GEOSERVICES SAMARINDA KALIMANTAN TIMUR (Jurnal Geomine, 2015)
Coal is strategic mineral and one of the national energy raw materials which have a major role in nation development.As for the methods used in data collection is to perform sample preparation by means of weighing grinding, mixing, drying, and milling, after it was analyzed Furnace TS to get a percentage of the sulfur content of sample. To the effect of observational is subject to be know total sulphur obstetric percentage in coal and sulphur content impact to its exploit in industrial area. Percentage titrates sulphur of five samples to analysis which is sample B1 has to titrate sulphur 1.56%, B2's sample has to titrate sulphur 1.16%, B3's sample has to titrate sulphur 1.23%, B4's sample has to titrate sulphur 1.43%, and B5's sample has to titrate sulphur 1.36%. Therefore of to five that sample at gets average value which is 1.34%. From to five sample that analyzed by averagely obstetric sulphur rate 1.34% on indecent to be utilized deep cements plant industrial area because overshot parameter which be needed which is maximal 0.80%, and as well as PLTU'S industry also because total its sulphur exceed requirement parameter which is maximal 0.40%.